ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MADRASAH ALIYAH PADA MATERI POLA BILANGAN - Shinta Mariam; Euis Eti Rohaeti; Ratna Sariningsih (Journal on Education, 2019)
This research was motivated to analyze students' mathematical problem-solving abilities. This research is a study that uses qualitative descriptive methods. The subjects of this study were class XII students, totaling 20 students in one of the Cimahi City Aliyah Madrasas. The stages of this research start from the process of planning, implementation, and observation. The instrument problem solving a mathematical problem that is given is a question that has been tested validation by mathematicians, amounting to 5 questions. From the results of the research that has been carried out, there are difficulties in students' difficulties in solving existing problems. Students who have low level of ability, difficulty factors that occur among them students have not been able to understand the problems faced with the problem, students still have difficulty in planning the completion model that will be used in answering each question, students also still not right to determine the next line in the arithmetic sequence. So that students cannot solve the problem of mathematical problem-solving skills properly.